A new species of Eupholus Boisduval from West New Guinea (Coleoptera: Curculionidae) - Riedel, Alexander; Porion, Thierry (Zootaxa, 2017)
Eupholus Boisduval is outstanding among weevils for its large body size and splendid coloration. Nevertheless, some species have eluded discovery until recently. Here we describe E. marielaurae sp. n. from the Arfak Mountains of West New Guinea. We provide morphological and molecular characters to differentiate it from E. cuvierii (Guérin-Méneville).